PENINGKATAN LITERASI DAN PELATIHAN FINANCIAL TEKNOLOGY BAGI MAHASISWA DAN DOSEN DI UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Yosephine Natalita Sembiring; Dimita H. P. Purba; Melanthon Rumapea; Rintan Saragih; Duma M. Elisabeth; Thomas Sumarsan Goh; Sahala Purba; Arison Nainggolan; Rimky M. P. Simanjuntak; Rahel Junita; Tri Darma Sipayung; Apriani M. Sibarani (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Financial Technology, also known as FinTech, is digital finance which is currently on the rise. People have started to get used to using it, although some still feel foreign. While the benefits felt by the presence of FinTech are quite positive because they can increase the effectiveness and efficiency of time. We can find one of its uses in the marketplace. This community service activity is carried out in the St. Catholic University environment. Thomas Medan as a partner for students and lecturers. This service activity focuses on training and increasing financial technology literacy. While the output of this activity is increasing the readiness of partners in using fintech so that partners as a community can support financial inclusion to access and use the full services of existing financial institutions in a timely, more informative manner at a relatively low cost.